Beyond depletion: Daily self-control motivation as an explanation of self-control failure at work - Wilken Wehrt; Anne Casper; Sabine Sonnentag (Journal of Organizational Behavior, 2020)
The organizational self-control literature usually applies resource perspectives that explain self-control failure at work by depletion of self-control resources. However, these perspectives neglect the role of self-control motivation. On a daily level, we examine several self-control aspects (resources, motivation, demands, and effort) as predictors of a manifestation of self-control failure at work, namely, daily counterproductive work behavior toward the organization (CWB-O). Additionally, we investigate self-control effort as a mechanism predicting the depletion of self-control resources throughout the day. We analyzed data from 155 employees in a 2-week diary study with 2 daily measurement points. Multilevel path modeling showed that self-control motivation and self-control demands, but not self-control resource depletion, predicted self-control effort. There was an indirect effect from self-control motivation on CWB-O via self-control effort but no indirect effect from self-control demands on self-control resource depletion throughout the day via self-control effort. Findings suggest that self-control motivation is a crucial factor explaining self-control failure at work and cast further doubt on the idea that exerted self-control effort is the only mechanism leading to self-control resource depletion.
Keywords: 650; CWB-O; diary study; ego depletion; self-control; self-control demands